1997
DOI: 10.1897/1551-5028(1997)016<1716:tohtha>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Hexachlorobenzene to Hyalella Azteca and Chironomus Tentans in Spiked Sediment Bioassays

Abstract: Abstract-Fourteen-day, whole-sediment toxicity tests using the amphipod Hyalella azteca and the midge Chironomus tentans were conducted on spiked sediment samples representing a range of hexachlorobenzene (HCB) concentrations. High rates of survival and growth relative to controls were observed in both test species. No observed effects concentrations (NOECs) were equal to the highest HCB concentration tested (42 mg/kg, normalized to 1% total organic carbon). Available literature on the aquatic toxicity of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Toxicity data for T. battagliai in the Guadalquivir Estuary and the Bay of Algeciras showed this species to be more sensitive in the sediment assays than C. closterium. This higher sensitivity can be explained by the nature of this species' relationship with sediment particles: T. battagliai has several different exposure routes, including direct contact with sediment through the body surface and ingestion of particles, as reported by Arau ´jo et al [6] However, the role of ingested particles is less clear because the extent to which sediment particles are ingested is not well known [33]. A toxicity gradient was observed for both organisms to the Rı ´a of Huelva samples.…”
Section: Resultsmentioning
confidence: 90%
“…Toxicity data for T. battagliai in the Guadalquivir Estuary and the Bay of Algeciras showed this species to be more sensitive in the sediment assays than C. closterium. This higher sensitivity can be explained by the nature of this species' relationship with sediment particles: T. battagliai has several different exposure routes, including direct contact with sediment through the body surface and ingestion of particles, as reported by Arau ´jo et al [6] However, the role of ingested particles is less clear because the extent to which sediment particles are ingested is not well known [33]. A toxicity gradient was observed for both organisms to the Rı ´a of Huelva samples.…”
Section: Resultsmentioning
confidence: 90%
“…Predicted effects thresholds were calculated for chlorobenzene, dichlorobenzenes, trichlorobenzenes, tetrachlorobenzenes, and penta‐chlorobenzene, but not for hexachlorobenzene. Previous research has demonstrated that hexachlorobenzene is unlikely to be a primary stressor in sediment [13, 14], because its low solubility relative to its toxicity apparently precludes direct toxic effects on aquatic organisms.…”
Section: Total Chlorinated Benzenes Modelmentioning
confidence: 99%
“…Predicted effects thresholds were calculated for chlorobenzene, dichlorobenzenes, trichlorobenzenes, tetrachlorobenzenes, and penta- chlorobenzene, but not for hexachlorobenzene. Previous research has demonstrated that hexachlorobenzene is unlikely to be a primary stressor in sediment [13,14], because its low solubility relative to its toxicity apparently precludes direct toxic effects on aquatic organisms. In addition to justifying the grouping of chlorinated benzene congeners by degree of chlorination, the QSAR approach could be incorporated in a probabilistic model by defining the relationship between PETs for different congeners based on published QSAR results.…”
Section: Interpretation Of Qsar Studiesmentioning
confidence: 99%
“…However, no chemicals other than HCBD were identified as potentially significant contributors to toxicity in any sample containing less than 3 mg/kg 1%OC HCBD. Specifically, hexchlorobenzene concentrations in all samples were well below the no‐effect concentrations observed in spiked sediment toxicity tests [9,34], toxic index values for other chlorinated benzenes [12] were well below levels expected to produce toxicity, and toxic index values for PAHs [11] were below the level associated with a 25% probability of toxicity. Additionally, Sferra et al [35] examined mercury concentrations in the dilution study as well as subsequent site‐specific tests and concluded that mercury‐related toxicity was not evident.…”
Section: Resultsmentioning
confidence: 99%